Experimental Study of Air-Steam–Mixture Condensation Underneath Containment Vessel Surface. (3rd August 2021) - Tan, Bing; Tian, W. X.; Chen, R. H.; Qiu, S. Z.; Su, G. H.
Abstract: Aiming at studying the condensate flow phenomenon and air-steam–mixture condensation heat transfer underneath a containment vessel surface, a test bench was constructed. The plate dimension was 1.5 × 0.6 m, with Carbozinc 11 coating on the surface, suspended in a pressure vessel with 2.5-m diameter and 4.5-m height. The air-steam mixture was condensed on an inclined plate through natural convection mode and jet mode. By observing flow behavior on the plate through a viewport, four basic regimes were obtained as the inclination angle gradually increased: droplet, droplet to rivulet transition, developed rivulet, and uniform film. During the experiment, we observed a steam atomization phenomenon; therefore, the model predicted better with the atomization effect considered. A simple formula from the condensation data is proposed when the air mole fraction is small. The error between the experimental results and the predicted data is within 25%.